"Fundamentals of Financial Management, 12th edition" - Brigham, Eugene F. (South-Western, 2012)
Count on the renowned author team that's First in Finance to deliver a unique balance of clear concepts, contemporary theory, and practical applications that ensures a thorough understanding of today's corporate finance and financial management. Brigham/Houston's FUNDAMENTALS OF FINANCIAL MANAGEMENT, 12E presents a solid, focused foundation in financial basics punctuated with timely actual examples, end-of-chapter applications, and Integrated Cases that make it easier to understand the how and why of corporate budgeting, financing, and working capital decision making. The book's presentation of Time Value of Money (TVM) is repositioned so readers can immediately begin using the concepts after learning them. THOMSON ONE-BUSINESS SCHOOL EDITION accompanies this edition, offering the same financial online database used by professionals on Wall Street every day. FUNDAMENTALS OF FINANCIAL MANAGEMENT, 12E also offers APLIA FOR FINANCE, the leading homework solution tool in educational publishing today. Trust the strengths in Brigham/Houston's market-leading FUNDAMENTALS OF FINANCIAL MANAGEMENT, 12E for the First in Finance time and time again.